Potensi Dan Tantangan Penerapan ArtificialIntelligence Dalam Bidang Pendidikan - Irvandy Anugrah Nasution; Jupriaman; Dwina Putri Dwina Putri; Muhammad Zulham Munthe (Insan Zenius Ilmiah, 2024)
The use of Artificial Intelligence (AI) in student learning is an increasingly relevant issue in the context of modern education. This article outlines the main issues by explaining the challenges and potential of AI in learning. The purpose of this article is to provide acomprehensive understanding of the role of AI in student learning in Indonesia. The research method used is a literature review, which includes the analysis of various sources and perspectives related to theuse of AI in higher education. The data used in this article is information from various literature sources, including research results, scientific articles, and news related to the implementation of AI in education. Examples of AI applications, such as chatbots for academic guidance, online learning systems, and automated assessments, were obtained from these sources. The results of the data analysis show thatthe use of AI in student learning has great potential to improve the quality of education, but it is necessary to pay attention to ethical challenges, the risk of dependency, and the important role of humaninteraction. Solutions such as AI ethics education, strict regulations, and the integration of AI with human interaction become integral parts of the conclusion of this article. In the era of digital transformation, adeep understanding of the role of AI in education, particularly in the context of chatbots for academic guidance, online learning systems, and automated assessments, is key to enhancing the quality of education and preparing students for a technology-driven future.